Reviews in Dynamic Characteristics of Rolling Interface and Vibration Test/Suppression Methods of the Rolling Mill - Fan, Xiao-bin; Li, Hao; Jiang, Yu; Fan, Bing-xu; Li, Liang-jing (Recent Patents on Engineering, 2021)
Background: Rolling mill vibration mechanism is very complex, and people have not found a satisfactory vibration control method. Rolling interface is one of the vibration sources of the rolling mill system, and its friction and lubrication state has a great impact on the vibration of the rolling mill system. It is necessary to establish an accurate friction model for the unsteady lubrication process of the roll gap and a nonlinear vibration dynamic model for the rolling process. In addition, it is necessary to obtain more direct and real rolling mill vibration characteristics from the measured vibration signals, and then study the vibration suppression method and design the vibration suppression device. Methods: This paper summarizes the friction lubrication characteristics of the rolling interface and its influence on rolling mill vibration, as well as the dynamic friction model of the rolling interface, the tribological model of the unsteady lubrication process of the roll gap, the non-linear vibration dynamic model of the rolling process, the random and non-stationary dynamic behavior of rolling mill vibration, etc. At the same time, the research status of rolling mill vibration testing technology and vibration suppression methods were summarized. Time-frequency analysis of non-stationary vibration signals was reviewed, such as wavelet transform, Wigner-Ville distribution, empirical mode decomposition, blind source signal extraction, rolling vibration suppression equipment development. Results: The lubrication interface of the roller gap under the vibration state presents unsteady dynamic characteristics. The signals generated by the vibration must be analyzed in time and frequency simultaneously. In the aspect of vibration suppression of the rolling mill, the calculation of inherent characteristics should be carried out in the design of the rolling mill to avoid dynamic defects such as resonance. When designing or upgrading the mill structure, it is necessary to optimize the structure of the work roll bending and roll shifting system, such as designing and developing the automatic adjustment mechanism of the gap between the roller bearing seat and the mill stand, adding floating support device to the drum shaped toothed joint shaft, etc. In terms of rolling technology, rolling vibration can be restrained by improving roll lubrication, reasonably distributing the rolling force of each rolling mill, reducing the rolling force of vibration prone rolling mill, increasing entrance temperature, reducing rolling inlet tension, reducing strip outlet temperature and reasonably arranging roll diameter. The coupling vibration can also be suppressed by optimizing the hydraulic servo system and the frequency conversion control of the motor. Conclusion: Under the vibration state, the lubrication interface of the roll gap presents unsteady dynamic characteristics. The signal generated by vibration must be analyzed by time-frequency distribution. In the aspect of vibration suppression of the rolling mill, the calculation of inherent characteristics should be carried out in the design of the rolling mill to avoid dynamic defects such as resonance. It is necessary to optimize the structure of work roll bending and roll shifting system, when designing or reforming the mill structure. In the rolling process, rolling vibration can be restrained by improving roll lubrication, reasonably distributing the rolling force of each rolling mill, increasing billet temperature, reasonably arranging roll diameter and reducing rolling inlet tension. Through the optimization of the hydraulic servo system and the frequency conversion control of the motor, the coupling vibration can be suppressed. The paper has important reference significance for vibration suppression of continuous rolling mill and efficient production of high quality strip products.
Keywords: vibration suppression